2014
DOI: 10.3928/00904481-20140723-11
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Dilemmas in Evaluating the Short Child

Abstract: Concerns about a child's growth are one of the most common topics parents voice during general pediatric office visits and are a leading cause for referral to a pediatric endocrinologist. There are a variety of conditions that lead to short stature in children; however, in the absence of true pathology, idiopathic short stature and constitutional delay are the most frequent causes. This article reviews the general approach to evaluating the short child and clinical signs that should prompt further evaluation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…GHD can only be diagnosed after extensive diagnostic procedures such as growth hormone (GH) stimulation tests [2,3,4,5]. Additionally, the cost-effectiveness in the differential diagnosis of short stature has so far been low [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GHD can only be diagnosed after extensive diagnostic procedures such as growth hormone (GH) stimulation tests [2,3,4,5]. Additionally, the cost-effectiveness in the differential diagnosis of short stature has so far been low [10].…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone deficiency (GHD) typically manifests at the age between 4 and 8 years presenting with growth failure, retarded bone age, and low serum levels of IGF-1 [1,2]. GHD has to be distinguished from other chronic diseases and especially from norm variants associated with short stature [2,3,4,5]. The most frequent underlying norm variants of short stature accounting for ∼80% of all cases visiting a pediatric endocrinologist are familial short stature (FSS) and constitutional delay of growth (CDG) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in growth velocity can be seen when reviewing a child's growth chart. Exact height measurements should be charted at all visits to observe and calculate a height rate (Garganta and Bremer, 2014). Therefore, plotting measurements on a growth chart is essential for recording a child's longitudinal development in size (National Center for Health Statistics, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported improved emotional and social functioning of GH‐treated children, while others found no change following GH therapy . In their systematic review, Gardner et al proposed that the inconsistency of the psychosocial outcomes may stem from methodologic flaws: referral bias, small numbers of participants, absent/inadequate control groups, lack of blinding and the relatively poor sensitivity of the explicit tools used to evaluate psychological functioning …”
Section: Introductionmentioning
confidence: 99%